Increased impacts of aircraft activities on PM2.5 concentration and human health in China - Qiang Cui; Zi-ke Jia; Xujie Sun; Ye Li (Environment International)
The rapid development of China’s aviation industry has caused a rapid increase in airport PM2.5 emissions. This study uses the Global Exposure Mortality Model (GEMM) to evaluate the monthly deaths caused by aircraft activities at 164 airports in China from 2015 to 2023, based on the PM2.5 concentration of airport aircraft activities and the detection data of the China National Environmental Monitoring Center, including twenty age groups, six diseases, and gender. This paper presents three main conclusions. Firstly, aviation PM2.5 emissions significantly impact mortality, with notable variations by year and season. The highest cumulative deaths are recorded in 2023, particularly in the third quarter, which peaked at 8,305 deaths. Despite the comparatively modest total of 11,604 deaths in 2022, a mere 0.2965 μg/m3 increase in PM2.5 concentration would precipitate an additional 39,138 deaths, representing a 1.05-fold rise from 2015. Secondly, the 80–84 age bracket exhibited the highest death proportion (16.51 %–18.73 %), while the 5–9 and 10–14 age groups had the lowest (0 %-0.13 %). Males aged 80–84 are the most affected demographic, with each 1 μg/m3 increase in PM2.5 leading to an additional 87 male deaths monthly in 2023, primarily from stroke and ischemic heart disease. In contrast, females only experienced 67 additional deaths per month from the same concentration increase. Lastly, airports in the economically vibrant Beijing-Shanghai-Guangzhou-Shenzhen region showed the highest mortality rates due to PM2.5 emissions. Airports in eastern coastal areas are more severely impacted than those in central and western China, revealing a spatial clustering of high death tolls in developed regions.